EFEITO DA CONTAMINAÇÃO CRÔNICA POR NEONICOTINOIDE NO PERFIL QUÍMICO CUTICULAR DE UMA VESPA SOCIAL - CHIROSA, Lucas Santos; BATISTA, Nathan Rodrigues; CARDOSO, Cláudia Andréa Lima; LIMA, Jean Carlos dos Santos; OLIVEIRA, Vinicius Edson Soares de; ANTONIALLI-JUNIOR, William Fernando (ANAIS DO ENIC, 2024)
-